TRANSFUSION SUPPORT IN MASS DISASTER BY ARMED FORCES INSTITUTE OF TRANSFUSION (AFIT): Transfusion Support - Ayyub, Mohammad; Hussain, Ch Altaf; Ghani, Eijaz; Ashraf, Muhammad (Pakistan Armed Forces Medical Journal, 2006)
Introduction Mass disaster is an unexpected event which results in wide spread damage to property, injuries & death; like air crash, train derailment & earthquake etc. As these causalities occur in a very short span of time therefore they outnumber, in severity and diversity, the medical resources to deliver comprehensive & definitive medical care to all victims. These events are “never typical”, but people who are involved in an aftermath are “always typical”. To manage these causalities paradigm is change from “application of unlimited resources for the greatest good of individual patient” to “allocation of limited resources for the greatest good of the greatest number”. The injuries in earthquake are mostly due to trauma, asphyxia, dust inhalation and exposure to extreme environment resulting in hypothermia. Therefore the injuries in such cases are broadly grouped into majority (minor cuts, bruises), small group (fractures) and minority (multiple fractures, internal injuries and crush syndrome). For adequate response of blood transfusion support, it is essential to have this background knowledge beside knowing the dynamics of flow of causalities.